A Synchronized Switching Technique for Elimination of Unexpected Output Pulses in Hybrid Active NPC inverter - Song, Min Geun; Kim, Seok Min; Lee, Kyo Beum (2019 IEEE 4th International Future Energy Electronics Conference, IFEEC 2019, 2019)
This paper proposes a synchronized switching technique to remove unexpected output pulses in Hybrid Active Neutral-Point Clamped (ANPC) inverters. The unexpected output pulse is generated at zero intersection point of the output voltage. Whereas, the reason of this pulse is due to the sudden effect of the deadtime on the switching time, in addition to another causes such as; the characteristic of digital calculation and etc. The unexpected output pulse distorts the output voltage, output current, and degrades the efficiency of the hybrid ANPC converter. Moreover, the unexpected output pulse may stress the switching devices as this pulse has momentary metrics. Therefore, the unexpected output pulses have to be removed. In these regards, A synchronized switching technique is proposed in this paper, while the proposed method is verified by simulation results.
Keywords: Active neutral point clamped; Output pulse; Silicon carbide devices; Synchronized switching; Three-level inverters; abnormal output pulse; hybrid active neutral point clamped inverter; silicon-carbide devices; synchronized switching; three-level inverters